A multinational randomised study comparing didactic lectures with case scenario in a severe sepsis medical simulation course. Issue 7 (27th July 2011) - Li, Chih-Huang; Kuan, Win-Sen; Mahadevan, Malcolm; Daniel-Underwood, Lynda; Chiu, Te-Fa; Nguyen, H Bryant
Abstract : Background: Medical simulation has been used to teach critical illness in a variety of settings. This study examined the effect of didactic lectures compared with simulated case scenario in a medical simulation course on the early management of severe sepsis. Methods: A prospective multicentre randomised study was performed enrolling resident physicians in emergency medicine from four hospitals in Asia. Participants were randomly assigned to a course that included didactic lectures followed by a skills workshop and simulated case scenario (lecture-first) or to a course that included a skills workshop and simulated case scenario followed by didactic lectures (simulation-first). A pre-test was given to the participants at the beginning of the course, post-test 1 was given after the didactic lectures or simulated case scenario depending on the study group assignment, then a final post-test 2 was given at the end of the course. Performance on the simulated case scenario was evaluated with a performance task checklist. Results: 98 participants were enrolled in the study. Post-test 2 scores were significantly higher than pre-test scores in all participants (80.8±12.0% vs 65.4±12.2%, p<0.01). There was no difference in pre-test scores between the two study groups. The lecture-first group had significantly higher post-test 1 scores than the simulation-first group (78.8±10.6% vs 71.6±12.6%, p<0.01). There was no difference in post-test 2 scores between the two groups. The simulated case scenario task performance completion was 90.8% (95% CI 86.6% to 95.0%) in the lecture-first group compared with 83.8% (95% CI 79.5% to 88.1%) in the simulation-first group (p=0.02). Conclusions: A medical simulation course can improve resident physician knowledge in the early management of severe sepsis. Such a course should include a comprehensive curriculum that includes didactic lectures followed by simulation experience.